Vestigial Is Required during Late-Stage Muscle Differentiation in Drosophila melanogaster Embryos - Deng, Hua (The American Society for Cell Biology, 2010)
The somatic muscles of Drosophila develop in a complex pattern that is repeated in each embryonic hemi-segment. During early development, progenitor cells fuse to form a syncytial muscle, which further differentiates via expression of muscle-specific factors that induce specific responses to external signals to regulate late-stage processes such as migration and attachment. Initial communication between somatic muscles and the epidermal tendon cells is critical for both of these processes. However, later establishment of attachments between longitudinal muscles at the segmental borders is largely independent of the muscle–epidermal attachment signals, and relatively little is known about how this event is regulated. Using a combination of null mutations and a truncated version of Sd that binds Vg but not DNA, we show that Vestigial (Vg) is required in ventral longitudinal muscles to induce formation of stable intermuscular attachments. In several muscles, this activity may be independent of Sd. Furthermore, the cell-specific differentiation events induced by Vg in two cells fated to form attachments are coordinated by Drosophila epidermal growth factor signaling. Thus, Vg is a key factor to induce specific changes in ventral longitudinal muscles 1–4 identity and is required for these cells to be competent to form stable intermuscular attachments with each other.